Portrait of Yoruba aesthetics in Saheed Osupa's fuji music (2018)
This paper examines how the subject of Yoruba aesthetics is constructed in the performance and works of Saheed Osupa, a prominentfuji music exponent in Nigeria. The study adopted discographic research approach and used purposive sampling technique to select Omoge, a track on Osupa's music album entitled Reliable. Recorded materials were transcribed and subjected to thematic and structural analyses. Ambivalences of postcolonial cultural production expressed in Omoge are marked ways by which Saheed Osupa's desire and clamour for character of beauty: a notable canon of Yoruba aesthetics are constructed. Textual analysis reveals a form of antinomy as signified by the way the musician tend to place a greater emphasis on dressing and artificial beauty than paying attention to a lady's good character, which is a more culturally acceptable inner form of beauty. Musical elements in Osupa’s works undulate between its through-composed formal structures to repetitiveness as a prominent compositional device. The paper stresses the futility in trying to separate the subject o' beauty from other well established virtuous attributes which the Yoruba hold so dear.